Exploring the Quality Parameters in Higher Education: A Factor Analysis Approach - Pratibha Saxena, Ankur Saxena, Nitika Vats Doohan, (European Economic Letters (EEL), 2023)
This research paper aims to investigate the quality parameters in Indian Higher Education institutions by analyzing the perceptions of students. It examines various factors related to learning environment, content of education, educational outcomes, research and scholarly ability, training and placement, internationalization, faculty characteristics, employee retention, administrative characteristics, reliability and viability of the university, safety measures, infrastructural facilities, and student welfare. The study utilizes a structured questionnaire to collect primary data from 600 students, and statistical analysis is conducted using IBM SPSS version 23. The reliability and validity of the instrument are assessed through Cronbach's alpha, indicating high internal consistency. Furthermore, exploratory factor analysis, specifically principal component analysis, is employed to identify underlying factors that represent the interrelationships among the quality parameters. The paper discusses the suitability of the data for factor analysis, as demonstrated by the high Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy (0.975) and the significant Bartlett's test of sphericity (p < 0.05). The factor extraction process involves determining the minimum number of factors required to represent the data set effectively. The eigenvalues and total variance explained are analyzed to determine the retained factors, which collectively explain a substantial portion of the total variance. By exploring the quality parameters in higher education institutions, this research contributes to understanding the factors that influence the overall quality of education in India. The findings can inform policymakers, university administrators, and other stakeholders in implementing measures to enhance the quality of higher education and meet the growing expectations for self-dependence in the country.